Generalized MINLP of Internet Pricing Scheme Under Multi Link QoS Networks - Fitri Maya Puspita; Irmeilyana Irmeilyana; Indrawati Indrawati (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
In this paper, we will generalize the multi link internet charging scheme in multi class QoS network. This scheme is designed according to the base price, quality premium and quality of service to help the service provider to set up the parameters to optimize the service provider’s profit and to serve better quality of service. The objective function is formed by setting up the base price as a constant and setting up quality premium as a parameter and a variable. Models are in form of Mixed Integer Nonlinear Programming Problem and are solved by using LINGO 13.0 to obtain the optimal solutions. The results show that in case when we set up the base price as a parameter with varying the quality premium, fixing the sensitivity price of user I in class j and also varying the sensitivity of class j, the highest optimal solution was achieved. The modified model also gives better optimal solution compared to original model. It means that by fixing base price, ISP is able to goal its objective by recovering cost and promoting certain services.